Bibliography: The Peruvian Revolutionary Process, First Phase - Soenens, Guido (1977)
This bibliography had its origin in two small compilations, one in charge of Henry Harman, functionary of United Nations, and the other by Teodoro Abanto, student of the Economics Program in Universidad del Pacífico. Those initial works gave a first idea of the dimensions that had the bibliography produced by the “Revolutionary Process of the Armed Forces”. The bibliographical records were put in chronological order. In the end, however, it is included a thematic index as a guideline for those who are interested in more specific aspects; the numeration of topics as well as the bibliography do not pretend to be exhaustive.